Study of biodiesel production from vegetable oils and its application in diesel engine - LEE, TONG MIN (Universiti Malaysia Sarawak (UNIMAS), 2009)
Biodiesel is one of the alternative fuels which are produced from transesterification of vegetable oil. Biodiesel production using waste vegetable oils is of great interest due to its low cost and the ability to recycle and reuse waste oils. This study concerns the efficient conversion of straight and waste vegetable oil to biodiesel and the assessment of vegetable oil biodiesel in terms of the resulted engine performance. Alkali-catalyzed transesterification of palm, sunflower, coconut and waste oils was carried out and the vegetable oil conversion to biodiesel efficiency is rated by the amount of biodiesel yield. Normal diesel B0 (i.e. 0% biodiesel and 100% diesel) and different types of biodiesel blends B10, B20, B30, B40 and B50 were tested in diesel engine and the engine performance was recorded. By using 1:1 volume ratio of methanol to vegetable oil and potassium hydroxide (KOH) catalyst, the conversion to palm oil biodiesel produced the highest yield. Conversely, conversion to waste vegetable oil biodiesel resulted in the lowest yield. Diesel engine fuelled with B50 coconut oil biodiesel blend resulted in lowest drop in engine power output and increment in specific fuel consumption if compared to using normal diesel. While fuelling with B50 waste vegetable oil biodiesel blend, it resulted in the lowest drop in mechanical efficiency. However, lower variation in engine performance is resulted when fuelling with lower biodiesel blend like B10 and B20.